Comparison of Compressive Strength of Five Hydraulic Cements - Akhavan Zanjani, Vagharedin; Sheikh-Al-Eslamian, Seyedeh Mahsa; Tabari, Kasra (Journal of Dental School, 2019)
Objectives: Maintaining pulp vitality is a main goal in restorative dentistry. Introduction of pulp capping agents paved the way to eliminate the shortcomings of these materials and obtain successful restorations. On the other hand, nanotechnology is an emerging field of science with increasing use in dental materials. This study sought to assess the effect of addition of nano-TiO2, nano-SiO2 and nano-Al2O3 on compressive strength of five hydraulic cements. Methods: In this in vitro, experimental study, three experimental formulations of nano hybrid MTA, MTA Angelus and MTA Angelus+ nano-oxide particles cements were placed in molds measuring 4±0.1mm in internal diameter and 6±0.1mm in height made of stainless steel (ISO9917-1). Ten samples were fabricated for each of the five groups of materials. Sound samples were stored at 37°C and 95±5% humidity and were subjected to compressive strength testing in a universal testing machine at a crosshead speed of 0.5mm/minute after 24 hours and one month. Two-way ANOVA, one-way ANOVA and independent samples t-test were used for comparison of compressive strength of groups at different time points. Results: The highest compressive strength belonged to MTA Angelus+ nanohydroxyapatite and nano-hybrid MTA C at 24 hours and 30 days, respectively. The lowest compressive strength belonged to nano-hybrid MTA B and MTA Angelus at 24 hours and 30 days, respectively (P<0.05). Conclusion: Addition of nanoparticles affected the compressive strength of cements. Compressive strength significantly increased over time in all groups.